Thirty-Sixth Annual Meeting of the American Malacological Union, Key West, Florida, July 16-20, 1970 (Hello World!, 1970)
The majority of the meetings were held in the convention hall, under the chairmanship of President Allen Solem. Ann Young welcomed members in attendance on behalf of the local committee and Roy C. Anderson and Mayor Dr. Delio Cobo on behalf of the Key West Convention Bureau and the City respectively on the first day July 16. A list of the papers presented is given below after an account of the distinctive social and field collecting events of the meeting.